COVID-19 cardiovascular epidemiology, cellular pathogenesis, clinical manifestations and management. (August 2020) - Sattar, Yasar; Ullah, Waqas; Rauf, Hiba; Virk, Hafeez ul Hassan; Yadav, Sunita; Chowdhury, Medhat; Connerney, Michael; Mamtani, Sahil; Pahuja, Mohit; Patel, Raj D.; Mir, Tanveer; Almas, Talal; et al.
Abstract: Coronavirus Disease 2019 (COVID-19) is a rapidly progressing global pandemic that may present with a variety of cardiac manifestations including, but not limited to, myocardial injury, myocardial infarction, arrhythmias, heart failure, cardiomyopathy, shock, thromboembolism, and cardiac arrest. These cardiovascular effects are worse in patients who have pre-existing cardiac conditions such as coronary artery disease, hypertension, diabetes mellitus, and coagulation abnormalities. Other predisposing risk factors include advanced age, immunocompromised state, and underlying systemic inflammatory conditions. Here we review the cellular pathophysiology, clinical manifestations and treatment modalities of the cardiac manifestations seen in patients with COVID-19.